Effects of Thermal Treatment and Storage on Hydroxymethylfurfural (HMF) Content and Diastase Activity of Honeys Collected from Middle Anatolia in Turkey - Turhan, Kadir (SPRINGER, 2009)
The composition and properties of honey are dependent on floral origins utilized by the bees and the climatic conditions of the area from which honey is harvested. Honey is a complex mixture, mainly composed of water, sugars (glucose, fructose, sucrose, maltose, and higher sugars), gluconic acid, lactone, nitrogenous compounds, minerals, and some vitamins. Novel studies oil physical and chemical properties of the types of honey produced in different countries have been reported by many scientists. Hydroxymethylfurfural (HMF) is a cyclic aldehyde that is produced by degradation of sugars. Several factors influence the formation of HMF in honey: temperature and time of heating; storage conditions; use of metallic containers and the chemical properties of honey, which are related to the floral source from which the honey has been extracted, these indicate pH, total acidity, mineral content; however, no information on the correlation between chemical characteristics and HMF level of the honey is available. This study has two goals: The first one is to investigate the effects of storage on HMF formation and diastase activity of honey. Second one is to determine HMF level and formation kinetics of honey after heating process. For this purpose 40 samples of honey were collected from Middle Anatolia and surrounding areas. The physicochemical properties of honey collected were determined. The obtained data were compared with results of other researchers.
Keywords: Anatolia; diastase activity; honey; hydroxymethylfurfural; QUALITY EVALUATION; Biochemistry & Molecular Biology; Chemistry